The Effect of Basil Essential Oil Addition on the Functional Properties of Gelatin-Based Edible Film - Ayu Lestari, Dwi; Fahrullah, Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Edible film is a thin film that can be consumed immediately and can be used as a food packaging material. The incorporation of basil essential oil is anticipated to enhance the functional characteristics of edible film. The objective of this study is to evaluate the impact of incorporating basil essential oil on the water vapor transmission rate, gelation time, and the chemical structure of gelatin-based edible films. The research method employed a completely randomized design, incorporating three distinct treatments and three replications to ensure the robustness of the findings. The treatments comprised K1, which did not include the addition of basil essential oil; K2, which incorporated 4% basil essential oil; and K3, which incorporated 8% basil essential oil. The results demonstrated that the incorporation of basil essential oil led to a significant (P<0.05) increase in the WVTR value, with elevated concentrations resulting in increased WVTR. However, the incorporation of basil essential oil did not demonstrate a statistically significant impact on the gelation duration (P>0.05). FTIR analysis revealed an interaction between essential oil and gelatin that affected the film structure, thereby increasing the flexibility and antibacterial potential of the film. In conclusion, the incorporation of basil essential oil has been demonstrated to enhance the functional properties of gelatin-based edible films.